(untitled) (Marketing Journal, 2025)
The article explores the potential of advanced technologies for developing competitive intelligence systems in enterprises. The advantages of Attention -LSTM and transfer learning models in predicting customer behavior and forecasting demand for new product s are highlighted. It is shown that machine learning technologies and the FBS -SE methodology play a key role in increasing production efficiency and accelerating decision -making. Digital transformation and green innovations are found 305 to have a positive impact on sustainable development and competitiveness. The research results provide practical recommendations for enhancing the effectiveness of competitive intelligence systems.